PENGARUH LOCUS OF CONTROL, INDEPENDENSI, DAN KOMPETENSI DALAM MENDETEKSI FRAUD (STUDI KASUS PADA BPK PERWAKILAN PROVINSI NTT) - as, Maria Chemy; Angi, Yohana Febiani; Tiwu, Maria I. (Universitas Nusa Cendana, 2023)
This study aims to determine the effect of locus of control, independence, and competence in detecting fraud. This research was conducted on examiners at the State Audit Board of the Province of NTT. The number of samples studied were 34 examiners. Data collection was done by using a questionnaire. The data analysis technique used is multiple linear regression analysis using the SPSS 26 application program. The results show that the locus of controland partial independence does not have a significant effect on the examiner's ability to detect fraud, while competence is partially affect the ability of examiners in detecting fraud. The results of the F test (simultaneously) show that locus of control, independence, and competence together have a significant effect on the examiner's ability to detect fraud, with a coefficient of determination of 45.7%.Keyword